Sale of credit portfolio and risk: the case of financial institutions in Brazil - Laureano, Graziella Lage (2009)
This study examines whether the sale of credit portfolios are used by financial institutions for risk management, according to Stanton (1998) and Murray (2001) or to capture resources, as indicated in Cebenoyan and Strahan (2001) and Dionne and Harchaoui (2003). Two hypotheses on credit portfolio sales were tested: 1) promote rating improvement to the remaining portfolio, or 2) drive to financial leverage - with worsening on the remaining portfolio -, controlling for recourse existence and to whom those assets were sold. The sample includes quarterly information from 145 financial institutions from the first quarter 2001 to second quarter of 2008. The results provide empirical evidence that financial institutions use these sales to improve the rating of the remaining credit portfolio, i.e. they transfer, in most cases, low quality assets, assuring good ratings and improving liquidity. Additionally, following Harchaoui and Dionne (2003) proposal - which besides testing, demonstrating that regulatory requirements promote leveraging in high-risk assets – it was observed the relationship between the Basel Index and credit portfolio rating. The conclusions were similar to those found by Dionne and Harchaoui(2003): the more adequate – higher Basel Index - the financial institution, the greater its chances of having a bad quality credit portfolio.